Ancillary Care in Community-Based Public Health Intervention Research - Merritt, Maria W. (American Public Health Association, 2010)
Community-based public health intervention research in developing countries typically takes place not in clinics but in people's homes and other living spaces. Research subjects and their communities may lack adequate nutrition, clean water, sanitation, and basic preventive and therapeutic services. Researchers often encounter unmet health needs in their interactions with individual subjects and need ethical guidelines to help them decide how to respond. To what extent do researchers have an ethical obligation to provide ancillary care—health care beyond what is necessary to ensure scientific validity and subjects' safety? We discuss a case example from Nepal and propose a simple 2-step sequence of questions to aid decision making.